EVALUASI PENDAMPINGAN KADER PADA PROGRAM APLIKASI SIPOCIS (SISTEM INFOMASI POSYANDU CIAMIS) DI DESA SADANANYA - Adzani, Alifa Maula; Alawiyah, Aini Zulfa; Nur Hidayah, Lutfia Nisa; Hamdan, Ahmad (Cendekia: Jurnal Pendidikan dan Pemberdayaan Masyarakat, 2024)
Ciamis Regency is one of the districts that has had innovations in the Posyandu data archiving system. This innovation aims to empower Posyandu Cadres in terms of orderly administration. The presence of the SIPOCIS application is a solution to prevent the loss of manual data archives in the form of Posyandu Information System books that are vulnerable to burning and loss. The research method used uses a qualitative approach that can be adapted as a forum for evaluating socialization programs and assistance in using the Sipocis application to Posyandu cadres with stages in the form of program implementation responses, program implementation alignment, and success after program implementation. At the time of implementation, the methods used were lectures, discussions, and implementation. Based on the results of the evaluation of the implementation of Socialization and Assistance in Using the Ciamis Posyandu Information System to Posyandu cadres, the results of the problem are lack of understanding in using the SIPOCIS application, lack of initiative in reminding Posyandu cadres related to data entry, and limited technology facilities owned by Posyandu cadres. Kirkpatrick in (Winaryati, 2021) developed an evaluation model, where this evaluation is very suitable for the assistance of the SIPOCIS application to cadres, because the Kirkpatrick model program evaluation is used to evaluate training programs carried out by Reaction, Learning, Behavior and Result.